The impact of sofosbuvir/daclatasvir or ribavirin in patients with severe COVID-19. (19th August 2020) - Eslami, Gholamali; Mousaviasl, Sajedeh; Radmanesh, Esmat; Jelvay, Saeed; Bitaraf, Saeid; Simmons, Bryony; Wentzel, Hannah; Hill, Andrew; Sadeghi, Anahita; Freeman, James; Salmanzadeh, Shokrollah; Esmaeilian, Hani; et al.
Abstract: Objectives: Sofosbuvir and daclatasvir are direct-acting antivirals highly effective against hepatitis C virus. There is some in silico and in vitro evidence that suggests these agents may also be effective against SARS-CoV-2. This trial evaluated the effectiveness of sofosbuvir in combination with daclatasvir in treating patients with COVID-19. Methods: Patients with a positive nasopharyngeal swab for SARS-CoV-2 on RT–PCR or bilateral multi-lobar ground-glass opacity on their chest CT and signs of severe COVID-19 were included. Subjects were divided into two arms with one arm receiving ribavirin and the other receiving sofosbuvir/daclatasvir. All participants also received the recommended national standard treatment which, at that time, was lopinavir/ritonavir and single-dose hydroxychloroquine. The primary endpoint was time from starting the medication until discharge from hospital with secondary endpoints of duration of ICU stay and mortality. Results: Sixty-two subjects met the inclusion criteria, with 35 enrolled in the sofosbuvir/daclatasvir arm and 27 in the ribavirin arm. The median duration of stay was 5 days for the sofosbuvir/daclatasvir group and 9 days for the ribavirin group. The mortality in the sofosbuvir/daclatasvir group was 2/35 (6%) and 9/27 (33%) for the ribavirin group. The relative risk of death for patients treated with sofosbuvir/daclatasvir was 0.17 (95% CI 0.04–0.73, P  =   0.02) and the number needed to treat for benefit was 3.6 (95% CI 2.1–12.1, P  < 0.01). Conclusions: Given these encouraging initial results, and the current lack of treatments proven to decrease mortality in COVID-19, further investigation in larger-scale trials seems warranted.